Urgensi Bahasa Arab di Era Teknologi - Na’im, Tsalisa Miftah Nur (Maliki Interdisciplinary Journal, 2026)
This study aims to examine the urgency of the Arabic language in the digital technology era and its learning strategies. The research employs a descriptive qualitative approach through literature review on the historical development of Arabic, its role in modern life, and innovations in learning methods. The findings reveal that Arabic holds a significant position not only as a religious language but also as a medium for global communication, access to knowledge, and digital da’wah. In the technological era, Arabic becomes increasingly relevant due to the support of various digital platforms that facilitate access to Islamic literacy and cross-cultural communication. Furthermore, Arabic learning strategies have transformed through the use of applications, social media, gamification, and interactive multimedia, making the learning process more effective and engaging. The integration of technology with conventional methods enhances learners’ motivation and competencies. Therefore, mastering Arabic is an essential requirement in facing globalization challenges. This study emphasizes that innovative and technology-based approaches are crucial to improve the quality of Arabic language learning in the modern era.